2017
DOI: 10.1186/s12859-017-1926-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of breast cancer subtypes by AP-ISA biclustering

Abstract: BackgroundGene expression profiling has led to the definition of breast cancer molecular subtypes: Basal-like, HER2-enriched, LuminalA, LuminalB and Normal-like. Different subtypes exhibit diverse responses to treatment. In the past years, several traditional clustering algorithms have been applied to analyze gene expression profiling. However, accurate identification of breast cancer subtypes, especially within highly variable LuminalA subtype, remains a challenge. Furthermore, the relationship between DNA me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…Such pathways included signaling pathways like EIF2 and AHR, as well as pathways involved in mitosis and other molecular mechanisms of cancer. Both sets of genes also contained many gene ontology (GO) biological processes pertaining to the cell cycle, consistent with previous studies that found such enrichment in basal-like subtypes of breast cancer (Yang et al, 2017;Yang, Gao and Luo, 2019). We further validated our results by testing for overlaps with known gene sets via GSEA analysis (Mootha et al, 2003;Subramanian et al, 2005).…”
Section: Numerical Examplessupporting
confidence: 88%
“…Such pathways included signaling pathways like EIF2 and AHR, as well as pathways involved in mitosis and other molecular mechanisms of cancer. Both sets of genes also contained many gene ontology (GO) biological processes pertaining to the cell cycle, consistent with previous studies that found such enrichment in basal-like subtypes of breast cancer (Yang et al, 2017;Yang, Gao and Luo, 2019). We further validated our results by testing for overlaps with known gene sets via GSEA analysis (Mootha et al, 2003;Subramanian et al, 2005).…”
Section: Numerical Examplessupporting
confidence: 88%
“…This unsupervised machine learning technique, also named co-clustering or subspace clustering, aims at discovering relevant local patterns in input data by extracting biclusters -submatrices with specific properties, e.g., with same values in certain rows or/and columns, correlated rows, or rows and columns, shift, scaled, or shift and scaled values in rows [9,24,30,36]. Since its first application to gene expression data over 20 years ago [7], biclustering and its algorithms have led to some meaningful discoveries in biology and biomedicine, including identification of biomarkers for cancer [42,43], diseases subtypes [8,22,47] or adverse drug effects [11].…”
Section: Introductionmentioning
confidence: 99%
“…GO term is a place to confirm data gene and protein Santamaria, Theron, and Quintales (2008). Another work was done by Yang, Shen, Yuan, Zhang, and Wei (2017), combining Affinity Propagation (AP) clustering and Iterative Signature Algorithm (ISA) biclustering to analyze breast cancer. From the mixed results of the two methods, nine biclusters were obtained.…”
Section: Introductionmentioning
confidence: 99%